THE RATIONALIZATION OF CURRICULUM DEVELOPMENT - Arini Gultom; Anis Natasha; Hesti Khairati Mardiyah; Syarah Vina Ain; Rora Rizki Wandini (JURNAL TARBIYAH, 2020)
For education units, the curriculum is very important. In order to attain a learning objective, the curriculum is very important to facilitate the learning process. With curriculum, it can be easier or help teaching staff in teaching. It is said that the curriculum is a tool or an intermediary to accomplish an objective at the educational level. There are already many curriculums in Indonesia, such as the 1947 curriculum  1952 curriculum  1975 curriculum  1994 curriculum 2004 curriculum (KBK), the 2006 curriculum (KTSP) and the lastest curriculum is the 2015 curriculum or what is called as the 2013 curriculum which is currently being used to date